2019
DOI: 10.3389/fphys.2019.00764
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Reveals Spatial and Sex Differences in Pectoralis Major Muscle of Broiler Chickens Contributing to Difference in Susceptibility to Wooden Breast Disease

Abstract: Wooden Breast Disease (WBD) is a novel myopathy affecting the pectoralis major muscle of modern broiler chickens. The etiology of WBD is not currently known, but has been linked to increased feed efficiency, growth rate, and muscle yield in broiler chickens. Differential effect of WBD has been detected between regions of the P. major and between sexes of broilers—male birds and the cranial aspect of the muscle tend to be more severely affected by the disease than females and the caudal aspect. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 71 publications
5
44
1
Order By: Relevance
“…The greater role of insulinindependent glucose transport in cardiac and smooth muscle allows glucose uptake even when glycolysis and glycogenesis are impaired. The importance of insulin-insensitive glucose transport in development of diabetic retinopathy (Kumagai, 1999), atherosclerosis (Wall et al, 2018), diabetic nephropathy (Brosius and Heilig, 2005), pulmonary fibrosis (Cho et al, 2017), diabetic myocardial fibrosis (Asbun and Villarreal, 2006;Gorski et al, 2019) and non-alcoholic fatty liver disease (Nanji et al, 1995) has been demonstrated and is in support of our hypothesis that wooden breast shares substantial etiological factors with type 2 diabetes in mammals.…”
Section: Insulin-independent Glucose Transport In Chicken Skeletal Musupporting
confidence: 79%
See 1 more Smart Citation
“…The greater role of insulinindependent glucose transport in cardiac and smooth muscle allows glucose uptake even when glycolysis and glycogenesis are impaired. The importance of insulin-insensitive glucose transport in development of diabetic retinopathy (Kumagai, 1999), atherosclerosis (Wall et al, 2018), diabetic nephropathy (Brosius and Heilig, 2005), pulmonary fibrosis (Cho et al, 2017), diabetic myocardial fibrosis (Asbun and Villarreal, 2006;Gorski et al, 2019) and non-alcoholic fatty liver disease (Nanji et al, 1995) has been demonstrated and is in support of our hypothesis that wooden breast shares substantial etiological factors with type 2 diabetes in mammals.…”
Section: Insulin-independent Glucose Transport In Chicken Skeletal Musupporting
confidence: 79%
“…Increased expression of LPL is a consistent and early signal of the overprovision of lipids to the pectoralis major in affected birds. LPL is upregulated in 2-and 3-week-old broilers that later develop wooden breast (Papah et al, 2018;Lake et al, 2019), it has been proposed as a contributor to sex-linked differences in wooden breast incidence rate and severity (Brothers et al, 2019), and its increased expression in affected birds has been localized to the site where disease is first microscopically apparent -the endothelium of veins undergoing phlebitis .…”
Section: Lipid Accumulation In Wooden Breast Phenotypementioning
confidence: 99%
“…Other molecules identified in IPA with changes in expression due to WB were JAKMIP2, which is invovlved in microtubule binding and CAPSL which is involved in calcium ion binding. This IPA pathway has also been detected when evaluating the PM of differential gene experssion between male and females birds with WB (Brothers et al, 2019).…”
Section: Organismal Metabolic Influence -Liver Transcriptomementioning
confidence: 86%
“…Research covering muscle myopathies in broilers reveals that myopathies have increased in recent years and have been correlated with the selection of larger breast muscle (Petracci et al, 2015). The cause of WB is currently unknown, but it is more prevalent in older, heavier male broilers than young birds (Kuttappan et al, 2017;Brothers et al, 2019). Larger breast muscle has been associated with hypertrophied muscle fibers which is thought to impact blood supply and number of satellite cells that are needed in muscle regeneration (Daughtry et al, 2017;Malila et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation